Screening for β-lactamase inhibitors from mangrove soil actinomycetes / Suhaidi Ariffin - Ariffin, Suhaidi (Institute of Graduate Studies, UiTM, 2016)
Marine-derived actinomycetes possess distinct and complex metabolic capabilities, resulting in the wide diversity of their secondary metabolites in terms of chemical structure and biological activity. The bioactive compounds of actinomycetes isolated from mangrove soils are reported to possess various biological activities such as antimicrobial, cytotoxicity, anticancer and antioxidant. The aims of this study are to isolate and characterize diverse populations of marine actinomycetes from mangrove soils, to identify selected morphologically distinct isolates by using 16S rRNA sequence analysis, to screen their potential biological activities as antimicrobial as well as β-lactamase inhibitor agents, and to elucidate the structure of selected bioactive compounds. A total of 73 actinomycete strains were isolated from 11 mangrove locations in Malaysia. Of these, morphological observations and 16S rRNA sequence analysis indicate the presence of representative species from at least 3 genera Streptomyces, Pseudonocardia and Saccharomonospora. The majority of the isolates belong to genus Streptomyces. It was found that the most productive medium for isolation is starch casein nitrate agar (SCNA)…